2018
DOI: 10.1039/c8ra07099g
|View full text |Cite|
|
Sign up to set email alerts
|

Sonodynamic therapy induces oxidative stress, DNA damage and apoptosis in glioma cells

Abstract: Malignant glioma remains one of the most challenging diseases to treat because of the invasive growth of glioma cells and the existence of the blood–brain barrier (BBB), which blocks drug delivery to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Literature data state that 260 nm is the characteristic wavelength of DNA due to π → π* transition of DNA bases and that DNA double-strand breaks provide an increase in absorption at 260 nm, i.e., a hyperchromic effect that can be used to evaluate the level of DNA damage. In our study, an increase in absorbance values at 260 nm was observed in the spectrum obtained after the interaction of dsDNA with Cu­(II) (Figure ), confirming that the DNA was damaged and underwent fragmentation and degradation …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Literature data state that 260 nm is the characteristic wavelength of DNA due to π → π* transition of DNA bases and that DNA double-strand breaks provide an increase in absorption at 260 nm, i.e., a hyperchromic effect that can be used to evaluate the level of DNA damage. In our study, an increase in absorbance values at 260 nm was observed in the spectrum obtained after the interaction of dsDNA with Cu­(II) (Figure ), confirming that the DNA was damaged and underwent fragmentation and degradation …”
Section: Resultssupporting
confidence: 75%
“…In our study, an increase in absorbance values at 260 nm was observed in the spectrum obtained after the interaction of dsDNA with Cu(II) (Figure 6), confirming that the DNA was damaged and underwent fragmentation and degradation. 42 3.5. Electrochemical Detection of DNA Damage in the Copper-Catalyzed System.…”
Section: Optimization Of the Experimental Conditionsmentioning
confidence: 99%
“…The majority of the cell-damaging effects induced by PDT and SDT are generally attributed to ROS. Sun et al (41) found that ROS were major triggering intermediates during the DVDMS-SDT treatment of human glioma U-373 MG cells, and that the increase in apoptosis was accompanied by an increase in cleaved-caspase 3 level and DNA fragmentation. Our study indicated that DVDMS-mediated PDT and SDT significantly inhibited the expression levels of PCNA and Bcl-xL, and enhanced cleaved-caspase 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the molecular mechanisms of SDT for GBM treatment through in vitro and in vivo experiments. Many drugs, including 5-ALA [ 44 52 ], fluorescein [ 53 ], rose Bengal [ 54 ], hematoporphyrin mono-methyl ether (HMME) [ 38 , 55 60 ], sino-porphyrin [ 61 63 ], photofrin [ 64 , 65 ], photolon [ 66 , 67 ], protoporphyrin IX (ppIX) [ 52 ], talaporfin sodium [ 52 ], aluminum phthalocyanine disulfonate (AlPcS 2a ) [ 68 , 69 ], and titanium dioxide (TiO 2 ), have been used as sonosensitizers [ 70 , 71 ], which mainly accumulate in the mitochondria (Table 1 ).…”
Section: Killing Mechanisms Of Sdtmentioning
confidence: 99%
“…Upon activation by US, ROS generation can result in a decrease in mitochondrial membrane potential (MMP) as well as mitochondrial swelling [ 46 , 48 , 54 , 56 58 , 61 , 63 ]. Meanwhile, the degradation of the sarcoplasmic/endoplasmic reticulum Ca 2+ ATPase (SERCA 2 ) in the endoplasmic reticular can lead to elevation of cytoplasmic Ca 2+ levels [ 56 , 58 ].…”
Section: Killing Mechanisms Of Sdtmentioning
confidence: 99%